Fruiting phenology is linked to rainfall variability in a tropical rain forest. (16th May 2018) - Dunham, Amy E.; Razafindratsima, Onja H.; Rakotonirina, Paul; Wright, Patricia C.
Abstract: As the influence of climate change on tropical forests becomes apparent, more studies are needed to understand how changes in climatic variables such as rainfall are likely to affect tree phenology. Using a twelve‐year dataset (2005–2016), we studied the impact of seasonal rainfall patterns on the fruiting phenology of 69 tree species in the rain forest of southeastern Madagascar. We found that average annual rainfall in this region has increased by >800 mm (23%) during this period relative to that recorded for the previous 40 years and was highly variable both within and between years. Higher monthly measures of fruiting richness and the intensity of fruiting in our sample community were associated with significantly higher levels of rainfall. We also found that less rainfall during the dry season, but not the wet season, was associated with a significant shift toward later timing of peak richness and peak intensity of fruiting in the subsequent 12 months; however, this pattern was driven primarily by an extreme drought event that occurred during the study period. Longer time scales of phenology data are needed to see whether this pattern is consistent. Madagascar is expected to experience more extremes in rainfall and drought with increasing climate change. Thus, the linkages between variable precipitation and the fruiting phenology of forest trees will have important consequences for understanding plant reproduction and the ability of Madagascar's wildlife to cope with a changing climate.